2021
DOI: 10.1007/s11604-021-01186-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly hypofractionated intensity-modulated radiation therapy for nonmetastatic prostate cancer with a simultaneous integrated boost to intraprostatic lesions: a planning study

Abstract: Ashida, Ryo ...[et al]. Highly hypofractionated intensity-modulated radiation therapy for nonmetastatic prostate cancer with a simultaneous integrated boost to intraprostatic lesions: a planning study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The longest reported follow-up time was 124 months [49]. In the planning studies, as shown in Table 2, the majority of studies utilized mpMRI for GTV delineation [10,18,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Five studies utilized PET-CT [12,[76][77][78][79][80], and four studies used "other methods" such as histopathology data or hypothetical IPLs [81][82][83][84].…”
Section: Statistics Of Reviewed Studiesmentioning
confidence: 99%
“…The longest reported follow-up time was 124 months [49]. In the planning studies, as shown in Table 2, the majority of studies utilized mpMRI for GTV delineation [10,18,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Five studies utilized PET-CT [12,[76][77][78][79][80], and four studies used "other methods" such as histopathology data or hypothetical IPLs [81][82][83][84].…”
Section: Statistics Of Reviewed Studiesmentioning
confidence: 99%